Dark Mode

4,890 views

23 votes

Let $a(x, y), b(x, y,)$ and $c(x, y)$ be three statements with variables $x$ and $y$ chosen from some universe. Consider the following statement:

$\qquad(\exists x)(\forall y)[(a(x, y) \wedge b(x, y)) \wedge \neg c(x, y)]$

Which one of the following is its equivalent?

- $(\forall x)(\exists y)[(a(x, y) \vee b(x, y)) \to c(x, y)]$
- $(\exists x)(\forall y)[(a(x, y) \vee b(x, y)) \wedge\neg c(x, y)]$
- $\neg (\forall x)(\exists y)[(a(x, y) \wedge b(x, y)) \to c(x, y)]$
- $\neg (\forall x)(\exists y)[(a(x, y) \vee b(x, y)) \to c(x, y)]$

58 votes

Best answer

$(\exists x)(\forall y)[(a(x, y) \wedge b(x, y)) \wedge ¬c(x, y)]$

$\quad \equiv ¬(\forall x)¬(\forall y)[(a(x, y) \wedge b(x, y)) \wedge ¬c(x, y)]$

$\quad (\because (\exists x) F(x) = \neg \forall x \neg F(x))$

$\quad \equiv ¬(\forall x)(\exists y)¬[(a(x, y) \wedge b(x, y)) \wedge ¬c(x, y)]$

$\quad (\because (\forall x) F(x) = \neg \exists x \neg F(x)), \neg \neg F(x) = F(x))$

$\quad \equiv ¬(\forall x)(\exists y)[¬(a(x, y) \wedge b(x, y)) \vee c(x, y)]$

$\quad \equiv ¬(\forall x)(\exists y)[(a(x, y) \wedge b(x, y)) → c(x, y)]$

(**C**) choice.

edited
Sep 18, 2018
by srestha

@akash

I thought it is logic programming

like this https://gateoverflow.in/958/gate2003-71

sorry misunderstood

1